Lithium ameliorates autistic-like behaviors induced by neonatal isolation in rats - Wu, Xiaoyan; Bai, Yanrui; Tan, Tao; Li, Hongjie; Xia, Shuting; Chang, Xinxia; Zhou, Zikai; Zhou, Weihui; Li, Tingyu; Wang, Yu Tian; Dong, Zhifang (Frontiers in Behavioral Neuroscience, 2014)
Neonatal isolation is a widely accepted model to study the long-term behavioral changes produced by the early life events. However, it remains unknown whether neonatal isolation can induce autistic-like behaviors, and if so, whether pharmacological treatment can overcome it. Here, we reported that newborn rats subjected to individual isolations from their mother and nest for 1 hr per day from postnatal days 1 to 9 displayed apparent autistic-like symptoms including social deficits, excessive repetitive self-grooming behavior, and increased anxiety- and depressive-like behaviors tested in young adult (postnatal days 42-56) compared to normal reared controls. Furthermore, these behavioral changes were accompanied by impaired adult hippocampal neurogenesis and reduced the ratio of excitatory/inhibitory synaptic transmissions, as reflected by an increase in spontaneous inhibitory postsynaptic current (sIPSC) and normal spontaneous excitatory postsynaptic current (sEPSC) in the hippocampal CA1 pyramidal neuron. More importantly, chronic administration of lithium, a clinically used mood stabilizer, completely overcame neonatal isolation-induced autistic-like behaviors, and restored adult hippocampal neurogenesis as well as the balance between excitatory and inhibitory activities to physiological levels. These findings indicate that neonatal isolation may produce autistic-like behaviors, and lithium may be a potential therapeutic agent against autism spectrum disorders during development.